Gestational age at term delivery and children's neurocognitive development. (15th July 2021) - Gleason, Jessica L; Gilman, Stephen E; Sundaram, Rajeshwari; Yeung, Edwina; Putnick, Diane L; Vafai, Yassaman; Saha, Abhisek; Grantz, Katherine L
Abstract: Background: Preterm birth is associated with lower neurocognitive performance. However, whether children's neurodevelopment improves with longer gestations within the full-term range (37–41 weeks) is unclear. Given the high rate of obstetric intervention in the USA, it is critical to determine whether long-term outcomes differ for children delivered at each week of term. Methods: This secondary analysis included 39 199 live-born singleton children of women who were admitted to the hospital in spontaneous labour from the US Collaborative Perinatal Project (1959–76). At each week of term gestation, we evaluated development at 8 months using the Bayley Scales of Infant Development, 4 years using the Stanford–Binet IQ (SBIQ) domains and 7 years using the Wechsler Intelligence Scales for Children (WISC) and Wide-Range Achievement Tests (WRAT). Results: Children's neurocognitive performance improved with each week of gestation from 37 weeks, peaking at 40 or 41 weeks. Relative to those delivered at 40 weeks, children had lower neurocognitive scores at 37 and 38 weeks for all assessments except SBIQ and WISC Performance IQ. Children delivered at 39 weeks had lower Bayley Mental (β = −1.18; confidence interval −1.77, −0.58) and Psychomotor (β = −1.18; confidence interval −1.90, −0.46) scores. Results were similar for within-family analyses comparing siblings, with the addition of lower WRAT scores at 39 weeks. Conclusions: The improvement in development scores across assessment periods indicates that each week up to 40 or 41 weeks of gestation is important for short- and long-term cognitive development, suggesting 40–41 weeks may be the ideal delivery window for optimal neurodevelopmental outcomes.